2020
DOI: 10.7759/cureus.8429
|View full text |Cite
|
Sign up to set email alerts
|

Acute Renal Failure in Critically Ill COVID-19 Patients With a Focus on the Role of Renal Replacement Therapy: A Review of What We Know So Far

Abstract: Acute renal failure remains a significant concern in all patients with the coronavirus disease 2019 (COVID-19) infection. Management is particularly challenging in critically ill patients requiring intensive care unit (ICU) level of care. Supportive care in the form of accurate volume correction and avoiding nephrotoxic agents are the chief cornerstone of the management of these patients. The pathophysiology of acute renal failure in COVID-19 is multifactorial, with significant contributions from excessive cyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(38 citation statements)
references
References 44 publications
2
30
0
3
Order By: Relevance
“…SARS-CoV-2 not only induces the diffused alveolar injury and acute respiratory failure, but also involves other organs, such as kidney and leads to renal resident cells injury (Huang et al 2020 ). AKI is a common feature of renal disease, occurred in 5–15% of patients with SARS- and MERS-CoV infection with higher rate of mortality (Raza et al 2020 ) In the first reports, the AKI incidence was few among COVID-19 patients. However, recent studies confirmed kidney failure in SARS COV2, related to the hospital death of cases with severe COVID-19 (Cheng et al 2020a ; Wang et al 2020d ).…”
Section: Covid- 19 and Renal Diseasesmentioning
confidence: 99%
“…SARS-CoV-2 not only induces the diffused alveolar injury and acute respiratory failure, but also involves other organs, such as kidney and leads to renal resident cells injury (Huang et al 2020 ). AKI is a common feature of renal disease, occurred in 5–15% of patients with SARS- and MERS-CoV infection with higher rate of mortality (Raza et al 2020 ) In the first reports, the AKI incidence was few among COVID-19 patients. However, recent studies confirmed kidney failure in SARS COV2, related to the hospital death of cases with severe COVID-19 (Cheng et al 2020a ; Wang et al 2020d ).…”
Section: Covid- 19 and Renal Diseasesmentioning
confidence: 99%
“…High creatinine levels were detected in individuals with severe cases of COVID-19 who were transitioning to multi-organ failure (28). Elevated creatinine serum levels are often corollary to comorbid diseases including diabetes, cancer, chronic renal failure, and some viruses, which can eventually lead to acute kidney injury (AKI) in severely ill and hospitalized patients, including COVID-19 patients (29,30). The development of AKI in patients with comorbidities is positively correlated with increased mortality.…”
Section: Gender Differences In Comorbidities and The Link To Creatininementioning
confidence: 99%
“…Altogether, these results indicate an association of AKI and mortality among COVID-19 patients (Table 2). Although studies showed a low rate of renal replacement therapy for COVID-19 patients with advanced AKI [19], this result explained by the high rate of mortality in advanced renal disease among patients suffering from SARS-CoV-2 infection. By this study, the risk of mortality in COVID-19 patients was strongly related to AKI (S.CR HR 44.23; 95% CI: 16.34, 119.70, p=0.000) and (BUN 13.04% versus 2.28%, HR 5.59, 95% CI: 1.86, 16.84, p=0.020) (Table 5, Fig.…”
Section: Discussionmentioning
confidence: 97%